PENGELOLAAN PUSAT LAUT SEBAGAI OBJEK WISATA BAHARI DI KABUPATEN DONGGALA - Rahman Tangngi Rerung; I Nyoman Slamet; Ni Wayan Sri Rahayu (STAH Dharma Sentana Sulawesi Tengah, 2026)
Pusat Laut Tourist Object Center in Kabupaten Donggala is one of the premier marine tourism destinations in Sulawesi Tengah that has great potential in the tourism sector. This study aims to analyze the management of the Marine Center as a tourist object using the management approach according to George R. Terry (2010), which includes the functions of planning, organizing, directing, and controlling. In addition, the analysis also refers to the 6M approach which includes Man (Manusia), Money (uang), Material (Barang), Machine (mesin), Method (metode), and Market (Pasar). The results of this study show that despite having great potential, the management of the Pusat Laut still faces structural and functional challenges that need to be systematically addressed, such as limited funding and infrastructure, lack of broad community involvement, weak promotion at the national and international levels, and a lack of synergy between local governments, villages, and the private sector